1997
DOI: 10.1172/jci119525
|View full text |Cite
|
Sign up to set email alerts
|

Nephropathy in human immunodeficiency virus-1 transgenic mice is due to renal transgene expression.

Abstract: HIV-associated nephropathy (HIVAN) is a progressive glomerular and tubular disease that is increasingly common in AIDS patients and one of the leading causes of end stage renal disease in African Americans. A major unresolved issue in the pathogenesis of HIVAN is whether the kidney disease is due to renal cell infection or a "bystander" phenomenon mediated by systemically dysregulated cytokines. To address this issue, we have used two different experimental approaches and an HIV-1 transgenic mouse line that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(160 citation statements)
references
References 42 publications
(36 reference statements)
4
155
1
Order By: Relevance
“…Studies of these mice, largely by the group of Klotman and their collaborators, have established that expression of HIV genes, presumably modeling the events of renal HIV infection, is sufficient to produce a renal injury in the mouse that is similar to HIVAN in humans. Studies in which kidneys from transgenic mice were transplanted into wild-type controls demonstrated that renal expression of HIV gene products was sufficient to initiate disease (8) and that systemic viral infection or other systemic conditions, such as the immunodeficiency that occurs in humans with HIVAN, were not necessary for the development of nephropathy. The murine models have been further refined to study the effects of selective transgenic insertion of specific HIV genes to determine their relative pathogenicity for the development of HIVAN.…”
Section: Hiv-associated Nephropathymentioning
confidence: 99%
“…Studies of these mice, largely by the group of Klotman and their collaborators, have established that expression of HIV genes, presumably modeling the events of renal HIV infection, is sufficient to produce a renal injury in the mouse that is similar to HIVAN in humans. Studies in which kidneys from transgenic mice were transplanted into wild-type controls demonstrated that renal expression of HIV gene products was sufficient to initiate disease (8) and that systemic viral infection or other systemic conditions, such as the immunodeficiency that occurs in humans with HIVAN, were not necessary for the development of nephropathy. The murine models have been further refined to study the effects of selective transgenic insertion of specific HIV genes to determine their relative pathogenicity for the development of HIVAN.…”
Section: Hiv-associated Nephropathymentioning
confidence: 99%
“…The homozygous transgenic mice develop cachexia and die by 2 months, a phenotype reminiscent of the AIDS-associated wasting syndrome (7,24,29,31). Development of HIVAN in this model depends on the presence of the HIV-1 genome in the kidney because wild-type kidneys transplanted into the HIV-1 trangenic background remain free of disease whereas transgenic kidneys transplanted into a wild-type background develop HIVAN (32).…”
mentioning
confidence: 99%
“…They carried out transplantation of kidneys between normal and HIV-transgenic mice. [1] These investigators showed that HIV-transgene-containing mice developed renal lesions that mimic HIVAN. This study suggested that the presence of HIV-1 gene products is necessary and sufficient in the development of renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The latter is characterized by focal glomerulosclerosis and tubulointerstitial lesions. [6] Acute renal failure has frequently been reported as a result of tubular cell injury (apoptosis and necrosis) in HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%